Simulação hidrológica e hidrossedimentológica em uma bacia com reservatórios com o modelo Soil and Water Assessment Tool (SWAT) - Guimarães, Camila Fonseca (2016)
Vegetation removal, and inadequate use and management of soil can change the hydrological cycle and, consequently, the hydrosedimentological cycle, by modifying sediment erosion and deposition. In addition to irregular use and occupation, construction of reservoirs also modifies the natural dynamics of rivers, interfering also in the transportation of solid particles, as it forms an artificial retention, which can cause settling and decrease the water quality due turbidity increasing. Aiming the estimating of flow and sediment production in watershed presenting reservoirs, this study used the mathematical model Soil and Water Assessment Tool (SWAT) as a tool, evaluating the influence of reservoirs retention. The resultsof modeling for the analyzed time period were compared to monitored data, and through the modeled parameters sensitivity analysis there wereidentified those that most influenced the results. The parameters were calibrated by using SWAT-CUP program. Once calibrated, the effectiveness of the program was evaluated statistically by using Nash-Sutcliffe (COE) efficiency coefficient , Trend Percentage (PBIAS), Mean Square Error (MSE) and coefficient of determination (R ²). In addition, it was evaluated how the presence of the reservoirs could influence the model. The insertion of reservoirs in watersheds modeling is very important once these water bodies can significantly affect the flow and the sediment production. However, the modeler must be careful about the proper insertion of their data, since the data quality influences the quality of the simulated model. The reservoir flow regime is the reservoir parameter that most affects the flow modeling. The specific parameter related to the reservoir that most affects the sediment production is the equilibrium sediment concentration (RES_NSED) since the user definition of the parameter will define the amount of sediment that will settle in the reservoir or pass to the downstream subbasins. The insertion of the reservoirs improved the sediment simulation, since the reservoirs served as sediment retention basins.